Precision wafer thinning and its surface conditioning technique. (14th January 2008) - Young, H-T.; Lin, C-C.; Liao, H-T.; Yang, M.
Experimental observations were conducted to investigate the effects of various parameters on the surface finish and SubSurface Damage (SSD) of ground silicon wafers. A novel design in wet chemical etching was proposed and implemented to provide wafers a means of strength enhancement while allowing the user to control the backside wafer surface finish. The results indicate that no propagating crystalline defect was accompanied, but leaving the wafer in a rather good surface integrity for back metal adhesion purposes.